Public Health in Europe : 10 years EUPHA (Italian Journal of Public Health, 2003)
What is Public Health (PH)? What are the links between Public Health research and policy in Europe? Where is PH coming from in the 20th century and where is it directed to?These are some of the questions addressed by Public Health in Europe – 10 years EUPHA, the volume, edited by Prof.W. Kirch and published by Springer in 2004, that presents a selection of the manuscripts from the 10th Annual Congress of EUPHA, held in Dresden in 2002.Gunnar Tellness, the President of EUPHA, reminds us what PH is, or what it should be: the science devoted to reduce in the population the amount of disease, premature death and disease-related discomfort, sickness and disability.In addressing these themes,Tellness suggests to improve PH by employing healthpromoting and cultural activities, in order to establish strong collaborations between public agencies, private business, organisations and pioneers.